Snert: Ritual-liturgical measurements and recipes for social capital - Wepener, Cas (Verbum et ecclesia, 2010)
The questions of how social capital is measured and how it is generated have received ample attention in recent years. This article is an attempt at making a modest contribution towards addressing these issues and specifically also as a contribution from the fields of Liturgical and Ritual Studies. It is argued that commensality can be taken as both lens/barometer with regard to the presence or absence of social capital, as well as being a potential generator of social capital. In order to arrive at this conclusion regarding food and the eating habits of humankind, the phenomenon of commensality and its relation to social capital is approached here from three different angles, namely Social Anthropology, New Testament Studies and Ethnography.